Antimicrobial Efficacy of Pometia pinnata Leaf Extracts Obtained by Ultrasound-Assisted Extraction with Choline Chloride:Citric Acid - Fasri Dian Safitri; Venty Wahyu Tariyani; Suhaera Suhaera; Nahrul Hasan; Putri Khaerani Cahyaningrum (Utan Kayu Publishing, 2026)
Bacterial and fungal infections, along with the rise of antimicrobial resistance, necessitate the exploration of novel natural antimicrobial agents. This study aimed to evaluate the efficacy of Pometia pinnata leaf extracts obtained using Ultrasound-Assisted Extraction (UAE) combined with a Natural Deep Eutectic Solvent (NADES) system based on choline chloride:citric acid, and to compare it with conventional methods. Various NADES molar ratios were tested to determine optimal conditions based on Total Phenolic Content (TPC) using the Folin–Ciocalteu method. Antimicrobial activity was assessed against Bacillus cereus, Shigella dysenteriae, and Malassezia furfur using disk diffusion and solid dilution methods. The results showed that the 1:3 molar ratio yielded the highest TPC (72.77±0.52 mg GAE/g). The NADES extract exhibited specific antibacterial activity against B. cereus (10.90±3.26 mm), while ethanol extracts were more effective against S. dysenteriae (11.78±0.98 mm). Against M. furfur, the NADES extract at 1,000 µg/disc demonstrated comparable activity to maceration at 6,000 µg/disc, with a Minimum Inhibitory Concentration (MIC) of 3,571 µg/mL. In conclusion, choline chloride:citric acid (1:3) NADES is an optimal green solvent for producing phenolic-rich extracts with specific and dose-efficient antimicrobial activity.